Urorectal Septum Malformation Sequence in A Calf - Kom, Mustafa; Eroksuz, Yesari (Kafkas Univ, Veteriner Fakultesi Dergisi, 2013)
Urorectal Septum Malformation Sequence was described in a 3-day-old, Simmental-Brown Swiss crossbred calf characterized by absence of anal and vaginal openings, ambiguous genitalia, sacral hypoplasia, anuria, colonic atresia and lumbal vertebral scoliosis.
Bir buza?ıda ürorektal septum malformasyon serisi
Keywords: Urorectal septum malformation sequence; Sacral hypoplasia; Anuria; Colonic atresia; Lumbal scoliosis; Calf